Community Empowerment through Utilization of Rice Husk Waste in Cirebon Regency - Rusmayadi, Gusti; Iffah, Nur; Ninasari, Anita; Laksmono, Rendro; Rais, Rinovian; Indriyani, Indriyani (LP2M INSURI Ponorogo, 2023)
The amount of rice production in Indonesia every year is always increasing. The results of the rice mill produce waste material, namely husks. Along with the increase in rice production, the amount of rice husk waste has also increased. The purpose of this service is to assist the community in utilizing husk waste to make a useful product. The approach used in implementing the KKN program for the people of Jagapura Kulon Village, Gegesik District, Cirebon Regency, is a Participatory Rural Appraisal (PRA) with five stages of design thinking. The dedication results show that the shoe rack and sandals that will be made use eco-friendly materials that use the waste from rice husks. The culture of reuse, reduce and recycle must also be applied to organic waste to reduce the use of new materials or materials. The manufacture of shoe and sandal racks is also expected to reduce the felling of trees used to make conventional shoe racks made of wood. Through RASENDAL products, we can reduce the use of new materials using unused waste.